Rola proroków w życiu politycznym Izraela w ocenie współczesnych egzegetów - Homerski, Józef (The Biblical Annals, 2017)
The article is part of the introductory chapter of a monograph on the subject: The Word of Jahwe about Nations in the Books of the Prophetic Writers. The author gives a review of the opinion of the exegetes of our century, on the question of whether the prophets were interested, and to what a degres, in political metters especially in those which concerned the relationship of the chosen people to its neighbours. The opinions of the exegetes in this matter are of a very wide range, from the extremity (the prophets are agents of foreign powers or they are utopians) — to level — hea ded opinions generally prevailling today, according to which the prophets were men of God engaged in political affairs in so far as the necessity of taking an interest in those problems was dictated by their mission and calling. The author considers that this statement is of great importance for further studies, because it should facilitate the correct interpretation of the prophecies of those men of God as to foreign nations.